Minute and Separate : Considering the Admissibility of Videotaped Forensic Interviews in Child Sexual Abuse Cases After Crawford and Davis - Chin, Kimberly Y (2010)
Child sexual abuse is one of the least prosecuted crimes in the United States in part because of the many evidentiary challenges prosecutors face. In 2004, the Supreme Court introduced a new standard for determining the admissibility of out-of-court statements made by declarants who are unavailable to testify at trial. In Crawford v. Washington, the Supreme Court held that testimonial statements are only admissible at trial if the declarant is unavailable to testify and there was a prior opportunity for cross-examination. This Note will examine Crawford’s impact on the admissibility of videotaped forensic interviews with child victims of sexual abuse and suggest that courts adopt a “minute and separate” approach when deciding whether statements contained in those interviews are testimonial in nature